ANALISIS KETERAMPILAN MENGADAKAN VARIASI PEMBELAJARAN TERHADAP PENINGKATAN HASIL BELAJAR SISWA SEKOLAH DASAR - Nurassyifa Qurotul Aini; Yeyen Sormin; Della Septia; Ramanda Putri Mardiyyana; Deti Rostika (STKIP Subang, 2023)
Observations made during observations at one of the elementary schools, the learning process carried out had not yet been created. The learning media used is also minimal, this is due to the limited media available. In practice, teachers more often use books when learning. The interaction pattern also looks monotonous, the teacher uses the lecture method more. The type of research used in this article is descriptive qualitative research. This research aims to describe one of the teachers' teaching skills, namely the skill of providing variety in elementary school classes. Variations in learning can create meaningful and enjoyable learning so that learning targets can be achieved.